Diabetic rats lose A2A receptor-mediated facilitation of ileal myenteric cholinergic neurotransmission - Monteiro, Salomé Gonçalves (2022)
Enteric dysmotility is a long-term complication of Diabetes mellitus that causes significant discomfort in 76% of diabetic outpatients. Knowing that purines may be involved in synaptic transmission modifications in the CNS of diabetic rats, we decided to investigate if purinergic dysfunction could also play a role in diabetic enteric neuropathy in rats.